The Social Movement of Coastal Communities in the Offshore Tin Mining Conflict in Batu Beriga Village, Central Bangka - Junio, Malvin; M. Adnan Madjid; Eko G. Samudro; Rachmat Setiawibawa; Arifuddin Uksan (Cita konsultindo, 2025)
This study examines the conflict between the coastal community of Batu Beriga Village, Central Bangka, and the state, represented by PT Timah, in offshore tin mining activities. This conflict arose due to the imbalance in power relations between the state's economic interests and local ecological sustainability. This study uses a qualitative descriptive method through literature study with social movement theory as an analytical tool. The results show that the Batu Beriga community's resistance movement against mining activities is a form of collective awareness and resistance to ecological injustice. This movement not only rejects resource exploitation but also fights for the rights to living space and ecological sovereignty of coastal communities. Therefore, resolving natural resource conflicts requires prioritizing participatory dialogue and reformulating marine spatial planning policies that are ecologically just and oriented towards the welfare of local communities.